The Calcium-Sensing Receptor Is Involved in Follicle-Stimulating Hormone-Induced Cumulus Expansion in in vitro Cultured Porcine Cumulus-Oocyte Complexes - Liu, Huage; Zhou, Dan; Liu, Cong; Zhuan, Qingrui; Luo, Yan; Mo, Xianhong; Fu, Xiangwei; Hou, Yunpeng (Frontiers in Cell and Developmental Biology, 2021)
The Calcium-Sensing Receptor (CASR) is a G protein-coupled receptor of the C family that reportedly promotes maturation of porcine oocytes. However, its role in cumulus expansion of cumulus-oocyte complexes (COCs) is not well known. This study was conducted to determine the role of CASR and potential mechanisms involved during in vitro maturation (IVM) of porcine COCs. After culture of COCs in follicle-stimulating hormone (FSH)-supplement maturation medium for 24 h, the time of breakdown of the germinal vesicle (GVBD), indicative of initiation of meiotic maturation, resulted in an increased (p < .05) CASR mRNA expression level in cumulus cells. Moreover, IVM of COCs in 10 μM of the CASR agonist NPS R-568 promoted (p < .05) cumulus expansion but only in FSH-containing medium. Conversely, 20 μM of the CASR inhibitor NPS2390 precluded cumulus expansion. We next tested the effect of the CASR agonist/inhibitor on the expression of cumulus expansion-related genes. The CASR agonist significantly upregulated the expression of hyaluronan acid synthase 2 (HAS2), whereas the CASR inhibitor downregulated the expression of all HAS2, prostaglandin-endoperoxide synthase 2 (PTGS2), and tumor necrosis factor a-induced protein 6 (TNFAIP6). Altogether, these results suggest that CASR activity is involved in FSH-stimulated porcine cumulus expansion.